Structure of a polymorphic repeat at the CACNA1C schizophrenia locus - Raquel Moya; Xiaohan Wang; Richard W. Tsien; Matthew T. Maurano (Proceedings of the National Academy of Sciences, 2025)
Genetic variation within intron 3 of the CACNA1C calcium channel gene is associated with schizophrenia and other neuropsychiatric disorders, but analysis of the causal variants and their effect is complicated by a nearby variable-number tandem repeat (VNTR). Here, we explored the structure and population variability of the CACNA1C intron 3 VNTR using 155 long-read genome assemblies from 78 diverse individuals. Based on sequence differences among repeat units, we clustered individual sequences into 7 VNTR structural alleles called Types. Three Types were related through large duplications, but the other Types diverged much earlier such that only 12 repeat units at the 5′ end of the VNTR were shared across most Types. The most diverged Types were rare and present only in individuals with African ancestry, but a multiallelic structural polymorphism was present across populations at different frequencies, consistent with expansion of the VNTR preceding the emergence of early hominins. We demonstrated that this polymorphism was in complete linkage disequilibrium with fine-mapped schizophrenia variants from genome-wide association studies (GWAS) and that this risk haplotype was associated with decreased CACNA1C gene expression in the brain. Our work suggests that sequence variation within a human-specific VNTR affects gene expression and provides a detailed characterization of new alleles at a flagship neuropsychiatric GWAS locus.